2023
DOI: 10.1007/s00421-023-05185-5
|View full text |Cite
|
Sign up to set email alerts
|

Remote effects of a 7-week combined stretching and foam rolling training intervention of the plantar foot sole on the function and structure of the triceps surae

Abstract: It is known that a single bout of foam rolling (FR) or stretching can induce changes in range of motion (ROM) and performance in non-directly adjoining areas of the dorsal chain (i.e., remote effects). However, to date, it is not known if such effects exist following long-term interventions. Thus, the purpose of this study was to investigate the remote effects of a 7-week combined stretching and FR training intervention of the plantar foot sole. Thirty-eight recreational athletes were randomly assigned to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…However, Konrad et al (2023) only found a statistically non-significant, moderate magnitude (p = 0.08, d = 0.5) increase in ankle dorsiflexion ROM. Consequently, according to the previous study of Konrad et al (2023) as well as of the findings in our current study, chronic ROM increases in non-treated areas (except for homologous contralateral effects) are very unlikely.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…However, Konrad et al (2023) only found a statistically non-significant, moderate magnitude (p = 0.08, d = 0.5) increase in ankle dorsiflexion ROM. Consequently, according to the previous study of Konrad et al (2023) as well as of the findings in our current study, chronic ROM increases in non-treated areas (except for homologous contralateral effects) are very unlikely.…”
Section: Discussionmentioning
confidence: 60%
“…Since foam rolling and stretching seem to have similar acute and chronic effects on ROM Wilke et al, 2020) the study of Konrad et al (2023) can be considered as relevant for our current data. However, Konrad et al (2023) only found a statistically non-significant, moderate magnitude (p = 0.08, d = 0.5) increase in ankle dorsiflexion ROM. Consequently, according to the previous study of Konrad et al (2023) as well as of the findings in our current study, chronic ROM increases in non-treated areas (except for homologous contralateral effects) are very unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations